2019
DOI: 10.1093/jxb/erz155
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary comparison of competitive protein-complex formation of MYB, bHLH, and WDR proteins in plants

Abstract: A protein complex consisting of a MYB, basic Helix-Loop-Helix, and a WDR protein, the MBW complex, regulates five traits, namely the production of anthocyanidin, proanthocyanidin, and seed-coat mucilage, and the development of trichomes and root hairs. For complexes involved in trichome and root hair development it has been shown that the interaction of two MBW proteins can be counteracted by the respective third protein (called competitive complex formation). We examined competitive complex formation for sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 76 publications
(119 reference statements)
1
42
0
Order By: Relevance
“…Three proteins were identified cluster with anthocyanin regulators PhAN2 and PhPHZ (Petunia x hybrida), AtPAP1(Arabidopsis thaliana) (Borevitz et al, 2000;Albert et al, 2011). Meanwhile, we found that LrAN1b and LrJAF13 were clustered into two clades, namely TT8 and GL3 clades, as previously described (Zhang B. et al, 2019). LrAN1b belongs to the TT8 clade, most homologous with StbHLH (Solanum tuberosum) and PhAN1(Petunia x hybrida), while another LrJAF13 was clustered with NtJAF13a, NtJAF13a (Nicotiana tabacum) and PhJAF13 (Petunia x hybrida) (Quattrocchio et al, 1998).…”
Section: Confirmation Of the Transcriptome Data Using Qrt-pcrsupporting
confidence: 77%
“…Three proteins were identified cluster with anthocyanin regulators PhAN2 and PhPHZ (Petunia x hybrida), AtPAP1(Arabidopsis thaliana) (Borevitz et al, 2000;Albert et al, 2011). Meanwhile, we found that LrAN1b and LrJAF13 were clustered into two clades, namely TT8 and GL3 clades, as previously described (Zhang B. et al, 2019). LrAN1b belongs to the TT8 clade, most homologous with StbHLH (Solanum tuberosum) and PhAN1(Petunia x hybrida), while another LrJAF13 was clustered with NtJAF13a, NtJAF13a (Nicotiana tabacum) and PhJAF13 (Petunia x hybrida) (Quattrocchio et al, 1998).…”
Section: Confirmation Of the Transcriptome Data Using Qrt-pcrsupporting
confidence: 77%
“…Partially redundantly regulates anthocyanin biosynthesis, trichome and root hair development [27,28,35,54,55].…”
Section: Bhlh002/gl3mentioning
confidence: 99%
“…In this complex, both the MYB and the WD40 proteins bind to the bHLH protein [35,47,48]. Moreover, this complex is proved to be conserved in plants during evolution [73,76,77], which regulates five processes, namely the production of anthocyanidin, proanthocyanidin, seed-coat mucilage, and trichomes and root hairs development [70]. For example, the roles of this complex in controlling the development of trichomes and root hairs are verified in many species, ranging from monocots (Z. mays) to dicots (Arabidopsis, Arabisalpina, Gossypium hirsutum and Petunia hybrida) [23,25,78].…”
Section: The Potential Roles Of Bhlhs In B Napus Rootsmentioning
confidence: 99%
“…For example, the roles of this complex in controlling the development of trichomes and root hairs are verified in many species, ranging from monocots (Z. mays) to dicots (Arabidopsis, Arabisalpina, Gossypium hirsutum and Petunia hybrida) [23,25,78]. And four residues of GL3 and EGL3 proteins are identified to be vital for the protein interaction, including Phe-177 of AtGL3, Pro-377 of AtGL3, Asp-477 of AtGL3 and Ser-589 of AtGL3 [70]. Similarly, these key residues are observed in BnbHLH orthologs as well (Additional file 1: Table S1), suggesting they may have the same/or similar roles in B. napus.…”
Section: The Potential Roles Of Bhlhs In B Napus Rootsmentioning
confidence: 99%